PELUANG HUBUNGAN KARAKTERISTIK MAHASISWA BARU DENGAN MOTIVASINYA MASUK ILMU KOMPUTER - Syarif Hidayatullah; Muhamad Saad Nurul Ishlah (KOMPUTASI, 2020)
Various motivational factors can influence prospective new students at Pakuan University (Unpak) when choosing a Computer Science Department as their majors. In order to be able to compete for better quality, Unpak is expected to be able to improve its excellent service, so that the needs and desires of the new students when deciding to join the Computer Science Department can be fulfilled. In this study, a survey of new students from the Department of Computer Science about their motivation to join the Department is conducted to find out what new students want when they decide to join. Furthermore, based on the survey, the Chi-Square method and Bayes method are used to get the probability of the relationship between the characteristics of new students and their motivation to go to the College when choosing the Department. The results show that there is a significant relationship between the characteristics of new students with motivation, which can be seen from the Gender, Regional Origin, Previous Information about Computer Science program and Computer Science Program Media including those that are combined in the above categories, except for Gender. It shows the greatest opportunity occurred in the characteristics of new students to the motivation of 1; 0.806; 0.750 and 0.742.